Экзистенциальные аспекты доверия - Джонсон, Дж.; Мельников, А. (Социология: теория, методы, маркетинг, 2009)
The paper offers interpretation of a trust phenomenon from positions of existential sociology (the approaches of the Californian school and E.Tiryakian). Authors pay attention to emergence, development, and infringement of trust at early life stages. The structure, levels, factors, and aspects of trust presented in various sociological and psychological researches are analyzed: basic trust/ basic distrust (E.Erikson); empathic optimal frustration (H.Kohut); trust to the world, trust to another and trust to own self (T.Skripkina); the personified and abstract trust, ontological security (E.Gid - dens); radiuses of trust (F.Fukujama); the rational credit of trust, the blind and naive trust, the cultural capital, a syndrome of distrust, paradoxes of democracy (P. Sztompka). Drawing from the data of annual public opinion surveys, the pheno menon of mass distrust in the Ukrainian society is discussed. Various existential aspects of trust, such as existential experience, ontologic safety, existential choice, absurdity and fear are highlighted and examined. It is emphasized that the problem of distrust in the Ukrainian society should be reoriented and reformulated as the problem of social justice which needs to be considered through a prism of existential experience.